Meeting society’s expectations of graduates: Education for the public good - Bennett, Dawn (Brill Sense, 2019)
Employability is a vital lynchpin in the balancing act between student, community, government and industry expectations of higher education and what the sector can deliver. The potential for higher education to educate for the public good has never been higher because the sector has never been larger or more diverse. In the year 1970, only 700 million people worldwide had accessed secondary or higher education; by the year 2100 this will have increased ten-fold to some seven billion people (Roser & Nagdy, 2018). Will there be seven billion graduate-level jobs by the end of this century? As I will argue in this chapter, access to jobs does not adequately describe the purpose of higher education. If higher education is to survive, the definition of employability, higher education’s role in its development and governments’ strategies for its measurement, must change. The exponential rise in post-primary education is indicative of global growth in higher education over the past four decades. To give a country-specific example, in 1971 only 2% of the Australian population had participated in higher education and this grew to almost 20% in the subsequent 40 years (Parr, 2015). In 2018, higher education engagement will have reached almost 50% of the Australian population (Roser & Nagdy, 2018).